Individual Companies as New Legal Entities in Law Number 11 of 2020 on Job Creation - Wiwin Budi Pratiwi (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
The government, through Law Number 11 of 2020 on Job Creation encourages the ease of doing business for Micro and Small Business actors with the formation of individual corporate legal entities. This policy of forming a private company is a new breakthrough from the government and can be used as a stimulus to restore economic conditions. The establishment of this individual company is further regulated in Government Regulation Number 8 of 2021 on Company Authorized Capital and Registration of Establishment, Amendment and Disbanding of Companies that Meet the Criteria for Micro and Small Businesses. The type of research used is normative juridical. The data analysis was conducted in a descriptive qualitative manner. The results show that this individual company is a new legal entity created by the rolling of the Job Creation Law. Business actors who will register an individual company must meet the criteria for micro and small businesses as stipulated in the provisions of laws and regulations regarding micro and small businesses regulated in the Law Number 20 of 2008 on Micro, Small and Medium Enterprises. Various facilities are provided to business actors, such as registering individual companies by filling out electronic forms and not requiring a notary deed. Business actors are facilitated by the existing regulations in the management of the company because as the sole owner, the existence of financial reporting obligations makes it easier to monitor the company's financial governance which is useful, especially for access to capital loans to banks.